Biosilicified oncolytic adenovirus for cancer viral gene therapy. (11th August 2020) - Kong, Hao; Zhao, Ruibo; Zhang, Quan; Iqbal, Muhammed Zubair; Lu, Jiaju; Zhao, Qingwei; Luo, Dandan; Feng, Cui; Zhang, Kangjian; Liu, Xinyuan; Kong, Xiangdong
Abstract : Biosilicified oncolytic adenovirus (OAs) significantly improved OAs distribution and tumor inhibition in vivo. Abstract : Oncolytic adenoviruses (OAs) have shown great potential for cancer viral gene therapy in clinical studies. To date, clinical trials have shown that the curative efficacy of OAs is still limited by hepatic sequestration and preexisting neutralizing antibodies (nAbs), which decrease the accumulation of the OAs in tumors. Herein, with the biosilicification method, we encapsulated an OA encoding the anticancer gene Trail (OA-Trail) with silica, which significantly improved virus distribution and tumor inhibition. In vitro and in vivo results indicated that compared with the native OA, biosilicified OA-Trail (OA-Trail@SiO2 ) showed significantly reduced viral clearance in the liver and evaded nAb degradation, inducing an efficacious anticancer effect under the premise of biocompatibility. These achievements present an alternative strategy involving biosilicification for enhanced OA-based cancer gene therapy.